(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The following article aims to evaluate, from a juridical perspective, the main matters related to plastic surgery on minors affected by Down syndrome, in particular analysing the health perception, the role of parents and the space for the freedom of the patient. Without taking into consideration the legitimacy of such interventions, the result is a clear call to action for the legal order to predispose adequate instruments to protect the right of individuals not to be standardised.